Quantitative Assessment of Mitral Inflow and Aortic Outflow Stroke Volumes by 3‐Dimensional Real‐time Full‐Volume Color Flow Doppler Transthoracic Echocardiography: An In Vivo Study. (1st January 2015) - Shimada, Eriko; Zhu, Meihua; Kimura, Sumito; Streiff, Cole; Houle, Helene; Datta, Saurabh; Sahn, David J.; Ashraf, Muhammad
Abstract : Objectives: Noninvasive quantification of left ventricular (LV) stroke volumes has an important clinical role in assessing circulation and monitoring therapeutic interventions for cardiac disease. This study validated the accuracy of a real‐time 3‐dimensional (3D) color flow Doppler method performed during transthoracic echocardiography (TTE) for quantifying volume flows through the mitral and aortic valves using a dedicated offline 3D flow computation program compared to LV sonomicrometry in an open‐chest animal model. Methods: Forty‐six different hemodynamic states in 5 open‐chest pigs were studied. Three‐dimensional color flow Doppler TTE and 2‐dimensional (2D) TTE were performed by epicardial scanning. The dedicated software was used to compute flow volumes at the mitral annulus and the left ventricular outflow tract (LVOT) with the 3D color flow Doppler method. Stroke volumes by 2D TTE were computed in the conventional manner. Stroke volumes derived from sonomicrometry were used as reference values. Results: Mitral inflow and LVOT outflow derived from the 3D color flow Doppler method correlated well with stroke volumes by sonomicrometry ( R = 0.96 and 0.96, respectively), whereas correlation coefficients for mitral inflow and LVOT outflow computed by 2D TTE and stroke volumes by sonomicrometry were R = 0.84 and 0.86. Compared to 2D TTE, the 3D method showed a smaller bias and narrower limits of agreement in both mitral inflow (mean ± SD: 3D, 2.36 ± 2.86 mL; 2D, 10.22 ± 8.46 mL) and LVOT outflow (3D, 1.99 ± 2.95 mL; 2D, 4.12 ± 6.32 mL). Conclusions: Real‐time 3D color flow Doppler quantification is feasible and accurate for measurement of mitral inflow and LVOT outflow stroke volumes over a range of hemodynamic conditions.